Bamboo in Disaster Management - Sobita Devi, Th.; Brojendro Singh, Th.; Amin, Syed Nusrat; Pinokiyo, Athokpam (Indian Forester, 2023)
Bamboo has significantly contributed to disaster management in North-Eastern region of India which is situated within disaster prone area of the country. Protection from almost all kinds of unavoidable natural calamities occurring in this particular region requires natural vegetation of bamboo or bamboo products in one form or another. The study highlights the potentials of bamboos in protection of landmass from destructions and disasters caused by natural calamities and in control of the consequences thereof. The paper concludes about the important measures to be taken up in future for utilization and conservation of bamboo for disaster management and future prospects.